In vitro and in vivo anti-tumor effects of brexpiprazole, a newly-developed serotonin-dopamine activity modulator with an improved safety profile - Suzuki, Shuhei (Oncotarget, 2019)
From the perspective of psycho-oncology, antipsychotics are widely used for patients with cancer. Although some antipsychotic drugs have anti-tumor effects, these antipsychotic drugs are not applicable for cancer patients because of their severe side effects. Brexpiprazole, a novel serotonin-dopamine modulator with an improved side effect profile, was developed as a drug that is structurally and pharmacologically related to aripiprazole, which was reported to have anti-cancer effects. However, it remains unknown whether brexpiprazole has anti-cancer effects. In this study, we examined whether brexpiprazole has anti-tumor effects in cancer cells and cancer stem cells (CSCs) of glioblastoma, pancreatic cancer, and lung cancer. Brexpiprazole suppressed cell growth and induced cell death in the cancer cells and the CSCs, and decreased the CSC properties of the CSCs. Brexpiprazole did not exert any cytotoxic effects on non-cancer cells at the anti-cancer effect-inducing concentration. In the cancer cells and the CSCs, brexpiprazole reduced the expression of survivin, an anti-apoptotic protein, whose reduction sensitizes tumor cells to chemotherapeutic reagents. In the preclinical model in which pancreatic CSCs were subcutaneously implanted into nude mice, brexpiprazole suppressed tumor growth, in addition to reducing the expression of Sox2, a marker for CSCs, and survivin. This suggests that brexpiprazole is a promising antipsychotic drug with anti-tumor effects and an improved safety profile.